2012
DOI: 10.1504/ijbge.2012.050040
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and its effect on the liquidity of a stock: evidence from the MENA region

Abstract: What causes investors to trade in certain stocks more than the others? We answer this question by documenting significant relationship between various proxies of corporate governance mechanisms and liquidity in the MENA region. Our results show that higher analyst following, lower ownership concentration, and having Big-Four auditors as external auditors lead to higher liquidity. All of these factors are considered to be the proxies of better corporate governance mechanisms. We argue that better corporate gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They found that a higher number of non-executive directors and more frequent board meetings are associated with higher stock market liquidity. Farooq and Seffar (2012) used the Big Four auditors, ownership concentration and analyst following as proxies of corporate governance. They found that these mechanisms have a positive correlation with stock market liquidity in the MENA region.…”
Section: Review Of Board Structure and Stock Market Liquidity Studiesmentioning
confidence: 99%
“…They found that a higher number of non-executive directors and more frequent board meetings are associated with higher stock market liquidity. Farooq and Seffar (2012) used the Big Four auditors, ownership concentration and analyst following as proxies of corporate governance. They found that these mechanisms have a positive correlation with stock market liquidity in the MENA region.…”
Section: Review Of Board Structure and Stock Market Liquidity Studiesmentioning
confidence: 99%
“…Although some previously published corporate governance studies related to the MENA (Middle Eastern and North African) region exist, they are mainly about individual or selected countries' or firms' practices at the micro level (e.g. Bremer & Ellias, 2007;Farooq & Chetioui, 2012;Farooq & Seffar, 2012;Kamal Hassan, 2012;Farooq & AbdelBari, 2013;Al-Malkawi et al, 2014). This paper covers the topic from the macro-level and regional-level standpoint through examining the corporate governance codes for all the sixteen MENA countries.…”
Section: Introductionmentioning
confidence: 99%